Twinning in metastable high-entropy alloys - Huang, Shuo; Huang, He; Li, Wei; Kim, Dongyoo; Lu, Song; Li, Xiaoqing; Holmström, Erik; Kwon, Se Kyun; Vitos, Levente (Nature communications, 2018)
Twinning is a fundamental mechanism behind the simultaneous increase of strength and ductility in medium- and high-entropy alloys, but its operation is not yet well understood, which limits their exploitation. Since many high-entropy alloys showing outstanding mechanical properties are actually thermodynamically unstable at ambient and cryogenic conditions, the observed twinning challenges the existing phenomenological and theoretical plasticity models. Here, we adopt a transparent approach based on effective energy barriers in combination with first-principle calculations to shed light on the origin of twinning in high-entropy alloys. We demonstrate that twinning can be the primary deformation mode in metastable face-centered cubic alloys with a fraction that surpasses the previously established upper limit. The present advance in plasticity of metals opens opportunities for tailoring the mechanical response in engineering materials by optimizing metastable twinning in high-entropy alloys. Twinning has been experimentally seen in high-entropy alloys, but understanding how it operates remains a challenge. Here, the authors show that twinning can be a primary deformation mechanism in three well-known medium- and high-entropy alloys that have unstable face-centered cubic lattices.